Banks' reserve management, transaction costs, and the timing of federal reserve intervention - Leonardo Bartolini; Giuseppe Bertola; Alessandro Prati (Federal Reserve Bank of New York, 2000)
We use daily data on bank reserves and overnight interest rates to document a striking pattern in the high-frequency behavior of the U.S. market for federal funds: depository institutions tend to hold more reserves during the last few days of each reserve maintenance period, when the opportunity cost of holding reserves is typically highest. We then propose and analyze a model federal funds market where uncertain liquidity flows transaction costs induce banks to delay trading bid up interest rates at end each period. In this context, central bank's interest-rate-smoothing policy causes high supply liquid be associated with around settlement days.
Keywords: G21; E52; 330; Mindestreservepolitik; Bankenliquidität; Geldmarkt; Theorie; USA